Conditions of effectiveness of methods of supporting women’s psychological well-being in situations of temporary relocation - Diana Saveikiene; Nataliia Dmytrivna Volodarska (Insight: the psychological dimensions of society, 2020)
Purpose. The article presents the research of problems of psychological assistance to women in temporary resettlement. Methods. Dialogue-phenomenological method, interviews, art-therapeutic methods: common drawings, “Wreath of Memories”. Results. The relevance of the research of the problem of individual’s psychological well-being in crisis situations is outlined. The urgent problems of psychological assistance to women temporary migrants who have undergone changes in social conditions are highlighted. Theoretical and methodological approaches to the problem of recovering and maintaining the psychological well-being of the individual are determined. The influence of psychological defense mechanisms of the personality on the social adaptation in the conditions of temporary resettlement is described. The particularities of application of group and individual psychotherapy techniques for activating the development of psychological well-being of personality are described. Conclusions. The effectiveness of techniques for emotional state psycho correction of temporarily resettled persons has been studied. It is determined that mobilization of women to the direct manifestations of their feelings, desires in dialogue with other persons, which intensifies their implementation, is an important condition for the effectiveness of the applied methods. Awareness and realization of these desires, openness in the manifestation of their desires, the manifestation of restrained emotions forms confidence in relationships with others, helps to maintain their own mental and physiological integrity. Possibilities of combination and use of art-therapeutic techniques and dialogue-phenomenological gestalt approach are determined. Recommendations for the organization of psychological assistance to women in recovering their psychological well-being are given. Means of conducting techniques for reducing emotional stress of the personality are selected. The analysis of obstacles in the social adaptation of the personality in crisis situations is carried out. The obtained empirical results of the study will contribute to effective organization of psychological support.